Identification and mechanism of peptides with activity promoting osteoblast proliferation from bovine lactoferrin. (April 2018) - Shi, Pujie; Liu, Meng; Fan, Fengjiao; Chen, Hui; Yu, Cuiping; Lu, Weihong; Du, Ming
Abstract: Lactoferrin (LF) is a basic glycoprotein and a dominant functional component from the whey protein in bovine milk. As a novel bone growth factor, it can fulfill its biological functions of preventing osteoporosis by regulating the growth and metabolic processes of bone. However, it has not been clarified that LF plays a role of osteogenesis in a form of molecular fragments after enzymatic digestion. In this study, a novel peptide with osteoblast proliferation activity, ENLPEKADRDQYEL, was identified using UPLC-Q-TOF-MS/MS and Mascot analysis. The mechanism of promoting proliferation of osteoblast activity was also analyzed by molecular docking. Results demonstrated that ENLPEKADRDQYEL can significantly promote the proliferation of osteoblasts. The main interaction forces of ENLPEKADRDQYEL with epidermal growth factor receptor (EGFR) were the hydrophobic and hydrogen bonding. ENLPEKADRDQYEL had similar target domain (Lys13-Leu14-Thr15-Gln16-Leu98-Ser99-Ser418) with the key structure of EGFR compared with epidermal growth factor (EGF). This work established a theoretical foundation for the peptide from lactoferrin used as a functional component in functional dairy products. Graphical abstract: Highlights: This work established a theoretical method to screen bioactive peptides from lactoferrin. ENLPEKADRDQYEL screened by molecular docking methods can play a promote osteoblast proliferation activity. The main interaction forces of ENLPEKADRDQYEL with EGFR were the hydrophobic and hydrogen bonding. Lactoferrin is an attractive raw material to generate peptides with promoting osteoblast proliferation activity.